Implementation of the Law on the Fulfillment of the Rights of Adopted Children After Court Determination - Fairah Sahrain (Estudiante Law Journal, 2026)
The purposeof this author is to find out and understand how the legal regulations for the fulfillment of the rights of adopted children and how to implement the fulfillment of the rights of adopted children after the court determination. Type penulisan empirical. The type of approach that is applied in this writing is a qualitative approach. The data collection techniques used in this writing are observation, interview, and documentation techniques. The resultsof the authors show that the legal implementation of the fulfillment of the rights of adopted children after court determinations must be carried out in full because the process of removing children is carried out through legal courts for children and to ensure that the adoption process in the future has certainty hukum. Parents who have carried out the adoption of children are fully responsible for the child they have appointed because with the adoption of the child, the transfer of all full responsibility for the child he has raised because the process of adopting this child has legal legality.